Experimental Study on a New Damper Using Combinations of Viscoelastic Material and Low-Yield-Point Steel Plates - Jiang, Huanjun; Li, Shurong; He, Liusheng (Frontiers in Materials, 2019)
To enhance the seismic resilience of coupled reinforced concrete shear walls, a new damper working in the replaceable coupling beam is proposed in present study. The new damper is a combination of metallic damper and viscoelastic (VE) damper. The metallic damper consists of an I-shaped steel beam with multiple low-yield-point steel plate webs paralleled to each other; the VE damper is composed of multiple layers of VE material bonded between multiple steel plates. Through the composite use of viscoelastic material and low-yield-point steel, the new damper is expected to work effectively against both the earthquake and the wind. To study the respective mechanical behavior of each component of the combined new damper, eight metallic dampers, two VE dampers, and one combined damper are tested under cyclic loading first. The variable parameters of the metallic damper are strength grade of web steel, web dimensions and end stiffener configuration. It is found that the effect of the strength grade of web steel is most significant. Compared with the metallic damper using the steel web with normal strength grade, the ductility, ultimate plastic shear rotation and cumulative plastic shear rotation of the damper using the low-yield-point steel web are much larger. The effect of web dimensions on the deformation capacity is slight. With the addition of end stiffener, plasticity concentrates thereby, which prevents the flange-to-end plate weld fracture. The VE damper exhibits extraordinary deformability. The storage modulus, shear loss modulus and loss factor of the VE material decrease with the increase of strain amplitude. The storage modulus and shear loss modulus of the VE material decrease slightly as the excitation frequency increases within the range between 0.1 to 1 Hz, and the effect of the excitation on the loss factor is not significant. At last, the combined damper, an assembly of one metallic damper component and two VE damper components, is tested, which exhibits stable hysteretic behavior and excellent deformability. The predicted yield shear strength and elastic stiffness agree well with test results.